The Irrigation Wheat Initiative for Wheat Policy and Sustainable Development in Ethiopia - Andualem, Habtamu Mossie (Acta Carolus Robertus, 2025)
Wheat remains an essential food crop globally, including Ethiopia, although production has to face many challenges. Where domestic production lags demand, wheat farming guarantees food security and promotes economic development in Ethiopia. Due to limited precipitation, irrigation is an essential component of wheat production in the country. The Ethiopian government started structural, economic, and sectoral changes in 2019, designating wheat as a strategic commodity to promote agro-industry, lower imports, turn toward exports, and create jobs across the value chain. Ethiopia’s wheat production in 2022/23 exceeded 7.2 million metric tons, a 23%–27% (1.3–1.5 million) increase in the area cultivated over more than 2.3 million hectares, 15%–18% (0.3–0.4 million) increase in productivity, and estimated 3.0 metric tons per hectare. Even with these advances, the full potential has not yet been realized since irrigation development has not been applied to its best advantage. This study explores the current situation regarding irrigated wheat production, based on a thorough survey of the relevant literature and on secondary data evaluated by descriptive statistical methods. Results suggest, that improving smallholder farmers’ output through irrigation, increased technical knowledge, changes in governmental frameworks, and investments in irrigation infrastructure can contribute to self-sufficiency of the country under current and future climate change conditions.